Respuestas

  • Usuario de Brainly
2014-01-09T00:29:53+01:00
1er ejercicio

(x^3+x^2+x+1)\cdot(x-1)=x^4+x^3+x^2+x-x^3-x^2-x-1\\(x^3+x^2+x+1)\cdot(x-1)=x^4-1


2do ejercicio

(x^2-xy-xz)\cdot(x+1)=x^3-x^2y-x^2z+x^2-xy-xz

3er ejercicio

 (x^2+3x-6)\cdot(x^2-x+1)=x^4-x^3-x^2+3x^3-3x^2+\\+3x-6x^2+6x-6\\ (x^2+3x-6)\cdot(x^2-x+1)=x^4+2x^3-4x^2+9x-6

4to ejercicio

(y^3-3x+x^2+2 )\cdot( x-2)=xy^3-3x^2+x^3+2x-2y^3+6x-2x^2-4\\(y^3-3x+x^2+2 )\cdot( x-2)=x^3-2y^3-xy^3-5x^2+8x-4

5to ejercicio

(x^3+x+4)\cdot(x^2+2)= x^5+2x^3+x^3+2x+4x^2+8\\(x^3+x+4)\cdot(x^2+2)=x^5+3x^3+4x^2+2x+8